The efficacy and safety of continuous versus single-injection popliteal sciatic nerve block in outpatient foot and ankle surgery: a systematic review and meta-analysis - Hsuan-Hsiao Ma; Te-Feng Arthur Chou; Shang-Wen Tsai; Cheng-Fong Chen; Po-Kuei Wu; Wei-Ming Chen (BMC Musculoskeletal Disorders, 2019)
Abstract Background Continuous popliteal sciatic nerve block (CPSNB) has been performed in outpatient foot and ankle surgery as a regional anesthesia method to relieve postoperative pain. Its efficacy as well as safety is yet to be established. There are two purposes of this study: (1) to validate the efficacy of CPSNB with regards to better pain relief and reduced analgesics consumption; (2) to assess the safety of CPSNB. Methods We performed a comprehensive literature review on Web of Science, the Cochrane Library, PubMed and Embase and only included randomized controlled trials (RCTs). Five RCTs that compared the efficacy and safety of CPSNB with the single-injection popliteal sciatic nerve block group were included. The primary outcome parameters were visual analog scale (VAS) scores at postoperative 24, 48 and 72 h. The secondary outcome parameters were amount of oral analgesics consumed, overall patient satisfaction and need of admission after surgery. A sensitivity analysis was performed to explore the consistency of the results. Results In comparison with the single-injection group, CPSNB was associated with a lower VAS score at postoperative 24 and 48 h (p < 0.05). There were no neuropathic symptoms or infection events after the nerve block. However, there were several minor complications associated with the pump and catheter system, with drug leakage being the most common complication (N = 26 of 187, 13.9%). Conclusion CPSNB is an effective method in pain management for outpatient foot and ankle surgery. Both methods appear to be safe as none of the patients experienced neuropathic symptoms or infection. Further studies with larger sample size are needed to compare the risk of major complications between the two methods. Level of evidence I; meta-analysis.